Fabry disease: Detection of Alu-mediated exon duplication by NGS. (June 2019) - Farr, Martin; Ferreira, Susana; Al-Dilaimi, Arwa; Bögeholz, Sonja; Goesmann, Alexander; Kalinowski, Jörn; Knabbe, Cornelius; Faber, Lothar; Oliveira, João Paulo; Rudolph, Volker
Abstract: Monogenetic diseases can be analyzed routinely by targeted DNA sequencing. If causative variants are not found, complementary methods like RNA sequencing or analysis of copy number variations by multiplex ligation-dependent probe amplification have to be considered. In the latter, especially exonic duplications or deletions can be detected, but the precise sites of mutations remain unclear. As we demonstrate in this casuistic report of Fabry disease, next-generation sequencing (NGS) of a long-range PCR product can identify the recombination site directly and illuminate the underlying molecular mechanism. Highlights: We performed diagnostic NGS of a long range PCR product for Fabry disease. A deep intronic recombination site was found, that could not be detected by routine Sanger sequencing. This report is the first description of an interchromosomal recombination between two Alu elements in the GLA gene. NGS of long-range PCR products is a straightforward method to detect and analyze intragenic rearrangements.